On the Generalised Anti-inverse Elasticity Rule: An Existence Result - Junichi Minagawa; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2018)
We consider an optimal commodity taxation problem under a consumption target and prove the existence of an optimal solution for the problem. This optimal solution obeys taxation rules that are contrary to standard taxation rules such as the inverse-elasticity rule. We also verify the necessary and sufficient condition for the optimal solution to exhibit uniform pricing.
Keywords: H21; 330; anti-inverse elasticity rule; consumption target; existence of an optimal solution; optimal commodity taxation; uniform pricing